Changes in stroke performance in 13-14 year old swimmers over an annual training cycle - Malinovsky, M. S.; Arishin, A. V.; Pogrebnoy, A. I. (Theory and Practice of Physical Culture, 2025)
The aim of the study is to identify the dynamics of kinematic parameters of stroke technique in swimmers aged 13-14 years in the structure of the annual cycle.